Analysis of leaf chlorophyll content of paddy plants during vegetative stage grown in soil media containing macroalgae organic fertilizer. Issue 1 (November 2021) - Kurniawan, N S H; Kirana, I A P; Abidin, A S; Jupri, A; Widyastuti, S; Hernawan, A; Nikmatullah, A; Sunarpi, H; Prasedya, E S
Abstract: Chlorophyll is a green pigment in leaves that functions to absorb light energy for photosynthesis. The value of chlorophyll concentration in leaves indicates the health status of a plant and healthy plants will produce more fruit. The purpose of this study was to determine the effect of chemical fertilizer (CF) and solid algae fertilizer (SAF) with different doses on the concentration of chlorophyll in paddy leaves. This research is important to do to determine the potential of macroalgae in reducing the dose of chemical fertilizer use in agricultural activities. In this study, paddy plants were given four different treatments, namely control (without CF and SAF); 100% chemical fertilizer (CF); 100% solid algae fertilizer (SAF); 50% chemical fertilizers and 50% solid algae fertilizers (CF+SAF). Each treatment consisted of ten pots. The results showed that the administration of SAF in the form of a combination of SAF 50% and CF 50% had a significant effect on the increase of chlorophyll b content of the leaves of paddy plants. However, there were no significant difference in chlorophyll a content between CF and CF+SAF group. Current results show that addition of SAF could potentially increase growth quality in paddy plants due to the increase of chlorophyll b content which absorbs higher frequency of blue light for photosynthesis.